2020
DOI: 10.3389/fphar.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Suppresses Glioma Vasculogenic Mimicry Formation and Angiogenesis by Blocking the PI3K/Akt/mTOR Signaling Pathway

Abstract: Angiogenesis and vasculogenic mimicry (VM) are thought to be the predominant processes ensuring tumor blood supply during the growth and metastasis of glioblastoma (GBM). Celastrol has potential anti-glioma effects, however the mechanisms underlying these effects remain unclarified. Recent studies have shown that the PI3K/Akt/mTOR signaling pathway is closely related to angiogenesis and VM formation. In the present study, we have demonstrated, for the first time, that celastrol eliminated VM formation by block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 97 publications
2
67
0
Order By: Relevance
“…28,29 Dysregulation of this pathway is also related to the therapeutic resistance of glioma. 30 With that, our results demonstrated that β-mangostin resulted in a significant induction of apoptosis and in a concomitant reduction of Akt phosphorylation at Ser473, which consequently inhibited PI3K/AKT/mTOR signaling pathway in C6 cells. In addition, flow cytometry analysis indicated that treatment of C6 cells with β-mangostin resulted in a significant induction of apoptosis.…”
Section: Discussionsupporting
confidence: 71%
“…28,29 Dysregulation of this pathway is also related to the therapeutic resistance of glioma. 30 With that, our results demonstrated that β-mangostin resulted in a significant induction of apoptosis and in a concomitant reduction of Akt phosphorylation at Ser473, which consequently inhibited PI3K/AKT/mTOR signaling pathway in C6 cells. In addition, flow cytometry analysis indicated that treatment of C6 cells with β-mangostin resulted in a significant induction of apoptosis.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, it is demonstrated that celastrol, an anti-glioma medicine, downregulated the HIF-1α, blocked the PI3K/Akt/mTOR signaling and disrupted angiogenesis and VM formation. [ 340 ]. mTOR, a downstream mediator in PI3K/AKT pathway, complicatedly regulated by HIF-1α signaling and acts as a nutrient/hypoxia sensor to modulate protein synthesis.…”
Section: Treatments Of Cancer Emphasize Microenvironment Hypoxia In Cmentioning
confidence: 99%
“…More importantly, previous studies have pointed out the significance of methylation levels at the paraoxonase 1 (PON1) and forkhead box protein M1 (FOXM1) promoter regions to the progression and development of RC ( 42 , 43 ), highly suggestive of the potential regulatory function of lncRNA IRAIN in the progression and development of RC involving other protein targets like PON1 and FOXM1. Also, VEGFA has been recognized to participate in tumorigenesis by mediating angiogenesis ( 44 , 45 ), yet we focused on the regulatory role of VEGFA in RC cell survival, migration, and invasion, underscoring the various forms of regulation of VEGFA in RC, which requires further investigation in the future. However, given the mounting evidence regarding the aberrant expression of VEGFA in RC ( 40 , 46 ), treatment modalities involving antibodies against VEGFA may hold therapeutic promise for RC management.…”
Section: Discussionmentioning
confidence: 99%